Design and Build of Electric Car Frame SULA Evolution - Adhan Efendi; Abu Rizal Fahmi (VANOS Journal of Mechanical Engineering Education, 2021)
This research is research and development. The purpose of this research is to make an electric car design drawing according to the national electric car race standards that have better dimensions and turbulence than the previous design. The method in designing an electric car frame is by observing and studying the literature. The results of data collection are selected and reviewed and a design is made according to standards. Supervise and evaluate so that design and manufacture are not much different. The results obtained in the design are (1) The design results in the manufacture of the Sula evolution electric car frame, there are two parts, namely the mainframe and the suspension frame. The frame is divided into several parts, namely the seat holder, battery holder, controller holder, and rollbar. While the suspension frame is the front arm and rear arm; (2) In the design of the Sula evolution electric car frame, the calculations carried out are using the Autodesk Inventor application and the formula in analyzing the results of the mainframe design for the Sula Evolution electric car, namely the calculation of the weight of the material based on the data taken from the design drawings made.